Rebel Universities in The Brazil of Anísio Teixeira: The University of The Federal District and The University of Brasília - Xavier, Libania (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
This article analyzes two higher education institutions created by Anísio Teixeira, identifying the autonomous and, to a certain extent. rebellious nature of the institutional model which defined their organization. It is divided into three parts. The first deals with the Brazilian educational debate which marked the 1930s and 1960s, in the middle of competing projects for national construction. Next, the proposal for the organization of the University of the Federal District and its characterization as a rebel university is discussed. The third part seeks to understand the positions of Darcy Ribeiro and Anísio Teixeira in relation to the proposal for the University of Brasília, highlighting its innovative and rebellious nature in relation to the models in force in the 1960s. Finally, Teixeira’s legacy is assessed and his contribution to current thinking about some of the most important themes related to higher education in Brazil.